Zipper Is Necessary for Branching Morphogenesis of the Terminal Cells in the Drosophila melanogaster’s Tracheal System - Jong-Hyeon Shin; Chan-Woo Jeong (Biology, 2021)
Branching morphogenesis and seamless tube formation in Drosophila melanogaster are essential for the development of vascular and tracheal systems, and instructive in studying complex branched structures such as human organs. Zipper is a myosin II’s actin-binding heavy chain; hence, it is important for contracting actin, cell proliferation, and cell sheet adhesion for branching of the tracheal system in post-larval development of the D. melanogaster. Nevertheless, the specific role of Zipper in the larva is still in question. This paper intended to investigate the specific role of Zipper in branching morphogenesis and lumenogenesis in early developmental stages. It did so by checking the localization of the protein in the cytoplasm of the terminal cells and also by analyzing the morphology of zipper RNAi loss-of-function mutants in regard to branching and lumen formation in the terminal cells. A rescue experiment of RNAi mutants was also performed to check the sufficiency of Zipper in branching morphogenesis. Confocal imaging showed the localization of Zipper in the cytoplasm of the terminal cells, and respective quantitative analyses demonstrated that zipper RNAi terminal cells develop significantly fewer branches. Such a result hinted that Zipper is required for the regulation of branching in the terminal cells of D. melanogaster. Nevertheless, Zipper is not significantly involved in the formation of seamless tubes. One hypothesis is that Zipper’s contractility at the lateral epidermis’ leading edge allows cell sheet movement and respective elongation; as a result of such an elongation, further branching may occur in the elongated region of the cell, hence defining branching morphogenesis in the terminal cells of the tracheal system.